A prescription for health: a primary care based intervention to maintain the non-smoking status of young people. (1st March 2001) - Fidler, Wendy; Lambert, Trevor W
Abstract : OBJECTIVES: To evaluate the effectiveness of primary health care teams in maintaining a group of young people aged 10–15 years as non-smokers. DESIGN: Randomised controlled trial using postal questionnaires. SETTING: Oxfordshire, UK. SUBJECTS: 2942 young people who were initially self declared non-smokers. INTERVENTION: Information about smoking, sent under signature of the subject's general practitioner, certificates and posters intended to reinforce non-smoking behaviour. MAIN OUTCOME MEASURES: Changes in smoking behaviour, attitudes measured after one year. RESULTS: After a year, smoking uptake was 7.8% in the control group compared with 5.1% in the intervention group (odds ratio (OR) 1.6, 95% confidence interval (CI) 1.1 to 2.2). Among boys the corresponding results were 5.2% and 2.4% (OR 2.3, 95% CI 1.2 to 4.6), and among girls 10.0% and 7.5% (OR 1.4, 95% CI 0.9 to 2.1). Among boys aged 14–15 the uptake rate was 12.8% in the control group compared with 5.4% in the intervention group. However, among girls of the same age the intervention was less effective, with smoking uptake of 15.1% in the control group and 12.8% in the intervention group. The intervention was more effective among young people whose initial attitudes identified them as definite non-smokers than those who were potential smokers. CONCLUSIONS: The intervention substantially reduced smoking uptake among the young people, particularly boys. Primary health care teams can play an important role in maintaining the non-smoking status of their young patients. Confidential postal contact from the doctor direct to the young person at home is influential and cost-effective.